An investigation of the success of comprehensive agricultural support programme projects on the farms allocated under land redistribution for agricultural development: a case study approach in the Waterberg District, Limpopo Province - Chabalala, Botana Robert (My University, 2008)
Land reform is divided into three sub-programmes, which are redistribution programmes, restitution and tenure reform. The redistribution programme consists of Land Redistribution for Agricultural Development settlement and non-agricultural enterprises. Land Redistribution for Agricultural Development programme was established to redress the imbalances of land owners aroused from the previous government and its policies. A person who qualifies to purchase farms through the Land Redistribution for Agricultural Development programme is a previously disadvantaged person, that is, an African, Coloured and Indian. If a person belongs to a previously disadvantaged group and that particular person works for the government he/she does not qualify to be funded by the Land Redistribution for Agricultural Development programme. The National Department of Agriculture introduced a new programme called the Comprehensive Agricultural Support Programme. The primary aim of the Comprehensive Agricultural Support Programme is to make provision for agricultural support to targeted beneficiaries of the land reform and agrarian reform programme. This dissertation proposed an investigation of the success factors of Comprehensive agricultural Support programme on the farms allocated under the Land redistribution for Agricultural Development in the Waterberg District of the Limpopo Province. The objectives of study were: i. To determine factors influencing the success of the Comprehensive Agricultural Support Programme projects on farms allocated under the Land Redistribution for Agricultural Development farms ii. To suggest recommendations for the improvement of the implementation of the Comprehensive Agricultural Support Programme. iv A case study approach was used to investigate the Comprehensive Agricultural Support Programme funded projects. Personal interview questions were posed to participants who were the farmers who receiving the Comprehensive Agricultural Support Programme grant and managers who were managing the Land Redistribution for Agricultural Development farms. Open-ended questionnaires were used to collect data and four farms allocated under Land Redistribution for Agricultural Development funded by the Comprehensive Agricultural Support Programme and four municipal managers in the Waterberg District of the Limpopo Province were interviewed. The qualitative approach was used to process the data The chapter layouts of this research are as follows: Chapter 1: Problem Statement, Aims and Objectives of the Study, Chapter 2: Literature Survey, Chapter 3: Research Design, Chapter 4: Analysis of Data and Interpretation, and Chapter 5: Recommendations and Conclusion. The analysis of the data revealed that Comprehensive Agricultural Support Programme is a success on the farms allocated under the Land redistribution for Agricultural Development in the Waterberg District of the Limpopo Province.
Thesis (MBA) -- University of Limpopo, 2008
Keywords: Land redistribution; Agricultural support programmes; Agricultural development projects -- South Africa -- Limpopo; Farms -- South Africa -- Limpopo; Land reform -- South Africa -- Limpopo